PPAT'S responsibility for deeds of sale and purchase made in his presence (Study of PPAT in Kupang City) - Jonneri Bukit; Rizky Tuahta Cristian Bukit (Journal of Law Science, 2023)
This research aims to describe the process of the birth of a sale-purchase deed, and find out how the responsibility of a Land Deed Official (PPAT). The research method used in this research is empirical normative research, with primary and secondary data types. The results show that the responsibility of PPAT in making land sale and purchase deeds regarding the form and procedure for making PPAT deeds is not only regulated in Government Regulation of the Republic of Indonesia Number 24 of 2016 concerning Amendments to Government Regulation Number 37 of 1998 concerning PJPPAT Articles 21-24 but also in Government Regulation No. 24 of 1997 concerning Land Registration which regulates this matter is confirmed in Article 38 paragraph (2) which determines "The form, content and method of making PPAT deeds are regulated by the Minister" (Minister of State Secretary). Before making a deed of sale and purchase of land rights, PPAT must first conduct an inspection at the local Land Office to find out the suitability of the certificate of land rights concerned with the existing registers at the Land Office by showing the original certificate to the Land Office officer. This examination needs to be done in order to avoid buying and selling land against fake certificates or double certificates or original but fake certificates (Asphalt). This is to avoid fraud in land transactions where it turns out that what is sold does not belong to the rightful seller.